Resposta de IgA, lgE, IgG e subclasses (IgG1 e lgG4) específicas a Candida albicans no soro e lavado vaginal de pacientes com Candidíase Vulvovaginal - Carvalho, Ricardo José Victal de (2003)
Vulvovaginal candidiasis is a gynecological pathology that is estimated that the majority of women will present at least one episode in the course of their life. Candida albicans it is the fungus most often involved in this pathology. The aim of this study was to determine the levels of anti-C IgA, lgE, IgG and subclasses (lgG1, IgG4). albicans in serum and vaginal lavage of women with or without vulvovaginal candidiasis to evaluate the role of these antibodies in the immunopathogenesis of this disease. Thirty patients with clinical symptoms of vulvovaginal candidiasis were selected (15 with positive vaginal secretion culture for C. albicans, 11 with negative culture and 4 with positive culture for Candida non-albicans and 12 asymptomatic control women. Serum samples and vaginal lavage were obtained for detection of anti-C. albicans antibodies by ELISA The results showed that symptomatic patients with positive culture had significantly higher levels of specific IgA in the vaginal lavage and lower in serum than those with negative culture. Serum levels of specific IgE were extremely high. low in relation to vaginal lavage.High levels of total specific IgG were found in vaginal C serum in both groups, regardless of the presence or absence of the fungus. Specific IgG1 and IgG4 levels were significantly higher only in the vaginal lavage of symptomatic patients with positive culture, with a slightly higher IgG1 / IgG4 ratio, indi cating that the IgG1 anticorphic response may be predominantly involved in the resolution of fungal infection. These results indicate that there is a marked response of IgA, IgG1 and IgG4 anti-C. albicans in the vaginal lavage of symptomatic patients with positive culture, suggesting an important role of these antibodies in the local immune response stimulated by the presence of the fungus.